2020
DOI: 10.1038/s41598-020-66029-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of land-atmosphere interaction parameters in hinterland of the Taklimakan Desert

Abstract: The importance of the energy exchange between the land surface and the atmosphere can be characterized by bulk transfer coefficients for momentum, C d , and heat, C h. The diurnal and monthly variations of both bulk transfer coefficients and lengths of surface roughness are analyzed. Based on observed data from January to December 2009 in hinterland of the Taklimakan Desert, the characteristics of aerodynamic roughness length, z 0m , and thermal roughness length, z 0h , are discussed. It should be noted that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 48 publications
4
7
2
Order By: Relevance
“…Figure 5(b) shows the variations in the surface albedo with the solar elevation angle in the desert area. According to the calculations, when the solar elevation angle was greater than 25°, the effect on the surface albedo was very limited, which is somewhat different from the results obtained in the Taklimakan Desert [41]. is difference was caused mainly by the latitude difference between the two locations.…”
Section: Effects Of Rainfall On the Surface Albedocontrasting
confidence: 73%
See 1 more Smart Citation
“…Figure 5(b) shows the variations in the surface albedo with the solar elevation angle in the desert area. According to the calculations, when the solar elevation angle was greater than 25°, the effect on the surface albedo was very limited, which is somewhat different from the results obtained in the Taklimakan Desert [41]. is difference was caused mainly by the latitude difference between the two locations.…”
Section: Effects Of Rainfall On the Surface Albedocontrasting
confidence: 73%
“…Figure 6(a) shows that the soil thermal capacity before the rainfall event was 1.09 × 10 6 J•m − 3 •K − 1 , which is close to the measured value of 1.12 × 10 6 J•m − 3 •K − 1 [42] in Dunhuang and slightly lower than the result of 1.56 × 10 6 J•m − 3 •K − 1 in the Taklimakan Desert [41]. After rainfall (Figure 6(b)), the soil thermal capacity increased to 1.54 × 10 6 J•m − 3 •K − 1 due to the increase in the VWC and a lower air content between sand particles, which resulted in an increase in the soil thermal capacity.…”
Section: Effects Of Rainfall On the Soilsupporting
confidence: 69%
“…The overall dynamic roughness of Shiquanhe Station on the Qinghai-Tibet Plateau is 5.8 × 10 −2 m. Wang et al [12] calculated and compared the dynamic roughness of different types of underlying surfaces in different regions of the Qinghai-Tibet Plateau and found that they were related to the vegetation, topography, soil state, and seasonal differences of the underlying surface. The annual aerodynamic roughness of the KLML station was 1.1 × 10 −2 m, which was higher than that obtained by Liu et al [17] in the hinterland of the Taklimakan Desert of 3.1 × 10 −3 m. He Qing et al [21] calculated the average roughness of Xiaotang Station to be 6.05 × 10 −5 m, Chen et al [22] calculated the aerodynamic roughness of Gansu Jinta Oasis Desert Station to be 2.8 × 10 −2 m, and Yang Xinhua et al [23] calculated the roughness of Hade Station in the northern edge of the Taklimakan Desert to be 2.70 × 10 −5 m, which is lower than that of Zhao et al [24]. The overall dynamic roughness of Shiquanhe Station on the Qinghai-Tibet Plateau is 5.8 × 10 −2 m. Wang et al [12] calculated and compared the dynamic roughness of different types of underlying surfaces in different regions of the Qinghai-Tibet Plateau and found that they were related to the vegetation, topography, soil state, and seasonal differences of the underlying surface.…”
Section: Aerodynamic Roughnesscontrasting
confidence: 69%
“…Several researchers used the wind speed profile method and wind tunnel simulation to study the dynamic roughness of a flat sandy bed and flat sand [13][14][15][16]. Liu et al [17] calculated multiple surface parameters in the hinterland of the Taklamakan Desert and found that the dynamic roughness in the region did not vary seasonally, mainly depending on wind speed. The C H is higher in winter and lower in summer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extreme precipitation events have occurred frequently (Wang et al., 2020; Zhang et al., 2012; Zhou et al., 2019). With the construction of the environment and climate observation network (Yang et al., 2021), it has been found that the land‐surface processes and the vertical structures of the atmospheric boundary layer are unique (Liu & Meng et al., 2020; Wang & Lu et al., 2016; Wei et al., 2019). Contrary to the typical 1,000–2,000 m over land, the convective boundary layer (CBL) can reach 5,000 m in summer (Wang & Wei et al., 2016).…”
Section: Introductionmentioning
confidence: 99%